LINC00494 Promotes Ovarian Cancer Development and Progression by Modulating NFκB1 and FBXO32 - Shu, Yang; Zhang, He; Li, Jinqiu; Shan, Yanhong (Frontiers in Oncology, 2021)
Background Ovarian cancer represents one of the most frequent gynecological cancers and is significant cause of death for women around the world. Long non-coding RNAs (lncRNAs) are recognized as critical governors of gene expression during carcinogenesis, but their effects on the occurrence and development of ovarian cancer require further investigation. In this report, we characterized LINC00494 as a novel oncogenic lncRNA in ovarian cancer. Methods Bioinformatics analysis predicted potential interactions among LINC00494, NFκB1, and FBXO32 in ovarian cancer, which were tested by dual-luciferase reporter assay, RNA pull-down, RIP, and ChIP assay. Cancer cells were transfected with relevant treated plasmids, followed by scratch and Transwell assays. The treated cells were injected into nude mice to establish a xenograft model for testing effects of LINC00494 and its target gene in vivo. Results LINC00494 and NFκB1 were highly expressed whereas FBXO32 had low expression in ovarian cancer cells and tissues. LINC00494 was found to bind NFκB1 and increase its activity, while NFκB1 was enriched at the FBXO32 promoter region, where it acted to reduce FBXO32 transcription. Overexpression of LINC00494 elevated NFκB1 expression and enhanced cell migration, invasion and tumorigenesis, but additional overexpression of FBXO32 interfered with the tumorgenicity of ovarian cancer cells in vitro and in vivo. Conclusion Our work demonstrated that LINC00494 promoted ovarian cancer progression by modulating FBXO32 via binding with the transcription factor NFκB1. These results provided new insight into the mechanism of ovarian cancer pathogenesis and suggested new therapeutic targets.